1996
DOI: 10.1172/jci118544
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme inhibition modulates endogenous endothelin in chronic canine thoracic inferior vena caval constriction.

Abstract: Endothelin (ET) is a potent vasoconstrictor peptide which is elevated in plasma in congestive heart failure. Recent studies suggest an important role for angiotensin II (AII) in the activation of ET in cultured cardiomyocytes. Chronic thoracic inferior vena caval constriction (TIVCC) is a model of reduced cardiac output that mimics the neurohumoral activation observed in congestive heart failure. We hypothesized that activation of the renin-angiotensin system in TIVCC plays a role in the activation of ET and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 36 publications
3
22
0
3
Order By: Relevance
“…6,21 In heart failure, the level of ET-1 has been shown to be elevated in the plasma; however, its local significance in the hypertrophic and failing myocardium remains unresolved. 22 In contrast to its potential as a cardiac growth factor and to its presumed concordant activation with the cardiac angiotensin system, 23,24 we observed that the cardiac ET-1 system was not activated in the established LVH stage. This observation was consistently supported by long-term bosentan treatment, which, in contrast to temocapril, did not diminish the progression of LVH.…”
Section: Iwanaga Et Almentioning
confidence: 58%
“…6,21 In heart failure, the level of ET-1 has been shown to be elevated in the plasma; however, its local significance in the hypertrophic and failing myocardium remains unresolved. 22 In contrast to its potential as a cardiac growth factor and to its presumed concordant activation with the cardiac angiotensin system, 23,24 we observed that the cardiac ET-1 system was not activated in the established LVH stage. This observation was consistently supported by long-term bosentan treatment, which, in contrast to temocapril, did not diminish the progression of LVH.…”
Section: Iwanaga Et Almentioning
confidence: 58%
“…14,31 Finally, the effect of ET blockade might be less pronounced when administered in the presence of an ACE inhibitor, because of the fact that chronic ACE inhibition inhibits the activation of the ET system. 32 Finally, it cannot be excluded that, in our experimental conditions, Tr already induces a maximal improvement of survival, excluding additional improvement after the combination therapy. In any case, whether a synergistic effect on long-term survival of concomitant ET A and ACE antagonism exists in humans is still unknown.…”
Section: Discussionmentioning
confidence: 80%
“…37 The salutary effects of ACE inhibitors are attributed to their actions on different pathways, including the modulation of endogenous ET concentrations and activity. 38,39 Drugs were given over a prolonged period in these studies, suggesting an antiatherogenic effect. 37 Hence, long-term inhibition of ET, blunting its atherogenic actions, 40,41 may also be beneficial.…”
Section: Discussionmentioning
confidence: 97%